Two New Species of Prαon Haliday (Hymenoptera: Aphidiidae) from Greece - Kavallieratos, Ν. G.; Lykouressis, D. Ρ. (ENTOMOLOGIA HELLENICA, 2000)
Two new species of Praon Haliday: P. staryi spec. nov. and P. athenaeum spec. nov., are described. P.staryi was collected and reared from Myzus nicotianae Blackman on Nicotiana tabacum L. and P. athenaeum from Hyperomyzus lactucae (L.) on Sonchus oleraceus L.